A comparison of analytical solutions of nonlinear complex generalized Zakharov dynamical system for various definitions of the differential operator - Melih Cinar; Ismail Onder; Aydin Secer; Mustafa Bayram; Abdullahi Yusuf; Tukur Abdulkadir Sulaiman (Electronic Research Archive, 2022)
This paper considers deriving new exact solutions of a nonlinear complex generalized Zakharov dynamical system for two different definitions of derivative operators called conformable and M− truncated. The system models the spread of the Langmuir waves in ionized plasma. The extended rational sine−cosine and sinh−cosh methods are used to solve the considered system. The paper also includes a comparison between the solutions of the models containing separately conformable and M− truncated derivatives. The solutions are compared in the 2D and 3D graphics. All computations and representations of the solutions are fulfilled with the help of Mathematica 12. The methods are efficient and easily computable, so they can be applied to get exact solutions of non-linear PDEs (or PDE systems) with the different types of derivatives.